Trapped by poverty, war, pestilence and disaster - Abd Razak, Dzulkifli (2006)
AS the year comes to a close, most are overwhelmed by a somewhat "sinking" feeling. A series of photographs published by Time (Dec 18) as "The Best Photos of 2006" with its tagline: "No ifs, ands or buts (http://www.time.com/time/yip/2006/)" reflects such a feeling. After all, a picture is worth a thousand words, especially when there is no word that can accurately describe the overall state of nearanarchy that the world has descended into over the last one year; and the emotions that spill over from it. Aptly so, Time wrote: "The biggest stories of the year, after all, were people trapped by war, poverty, disaster." Staring in the face, undoubtedly, is the bloody quagmire in Iraq as depicted by the classic picture of an Iraqi woman in despair witnessing a burning car, the result of a remotely detonated bomb in Baghdad’s central district of Karrada.